Radiology Technologists certified as Radioprotection Supervisors in Nuclear Medicine: current scenario (Brazilian Journal of Radiation Sciences, 2025)
The presence of a radiological protection supervisor is mandatory in the staff of a nuclear medicine service according to the CNEN-NN-3.05 standard. To obtain the certification of qualification as a radiological protection supervisor, it is necessary, in addition to taking the general and specific tests, to graduate from a higher education course recognized by the Ministry of Education in the areas specified by legislation. This study analyzed the number of professionals trained in radiology technology certified as supervisors of radiological protection in nuclear medicine in Brazil. For this analysis, only the list available on the regulatory agency's website up to the date of preparation of this study was considered. Of the 326 professionals found, only 2.76% have academic training in radiology technology, while physicists and physicians together represent more than half of the radiological protection supervisors (65.65%). These results show that, although the field of radiological sciences and the Radiology Technology course, specifically the one offered by the Federal University of Minas Gerais, allow students to complete their undergraduate studies able to enter this job market and act as radiological protection supervisors, there is a lower number of these professionals' certificates in this field. The study provided a parameter on the state of the art of higher education in Radiologic Technology and the insertion and interest of these professionals in certification when compared to other fields of study.
Keywords: Nuclear Medicine; Radiology Technology; radioprotection supervisors